Two vicious circles associated with the aging of the immune system in the development of severe forms of COVID-19 - Vrbic, Miodrag; Milinkovic, Ana (Frontiers in Aging, 2023)
The immune-inflammatory response is the basis of the pathophysiology of SARS-Cov-2 infection. In severe cases of COVID-19 uncontrolled systemic inflammatory response causes multiorgan dysfunction (MODS), as the most common immediate cause of death.Unfavorable outcome of the COVID-19 most often occurs in elderly patients. The aim of the study was to establish parameters with prognostic significance in severe cases of COVID-19 according to life years, laboratory markers of sepsis and MODS, as well as the number of peripheral CD4 + and CD8 + T lymphocytes in 20 consecutively selected critically ill patients.Eleven subjects were male, 9 female, mean age 73.45±11.59, among which the oldest patient was 94 and the youngest 43 years. All the patients met the sepsis and MODS criteria. Increased age and low CD4 + and CD8 + T cell counts were identified as independent predictors of death. Only the two youngest patients (43 and 50 years old) 2 survived 28 days, and they are the only ones with a CD4 lymphocyte count above 500 cells/mm 3 .Senescence of the immune system is mostly characterized by reduced regenerative capacity of adaptive immunity with diminished ability to respond to new antigens and a manifested proinflammatory phenotype. Additional reduction of protective capacity by further deterioration of T cell quantity and quality due to sepsis itself and mutual interaction of senescent T cells and vascular endothelial cells in the induction of cytokine storm represent two complementary vicious cycles in the development of sepsis-related multiorgan dysfunction.